Answer :

We, have AB =AC …(i)

and BX=BY …(ii)

According to Euclid’s axiom, if equals are subtracted from equasl, the remainders are equal.

So, on subtracting Eq.(ii) from (i) ,

We get, AB-BX = BC-BY

⇒ AX = CY [from figure]

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

In the Fig.5.12:<NCERT Mathematics Exemplar